2020
DOI: 10.15441/ceem.20.022
|View full text |Cite
|
Sign up to set email alerts
|

Long-term benefits of chest compression-only cardiopulmonary resuscitation training using real-time visual feedback manikins: a randomized simulation study

Abstract: Objective Cardiopulmonary resuscitation (CPR) education with a feedback device is known to result in better CPR skills compared to one without the feedback device. However, its long-term benefits have not been established. The purpose of this study was to evaluate the long-term CPR skill retention after training using real-time visual manikins in comparison to that of non-feedback manikins. Methods We recruited 120 general university students who were randomly divided into the real-time feedback group (RTFG) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
6
1
1
Order By: Relevance
“…It is remarkable that the participants were able to reach almost perfect compression depth during chest compressions and rescue breaths directly after the training and in the follow-up examination. These results are better than results of other studies ( 38 , 39 ). As a limitation, it must be mentioned that pre-training compression depth and rescue breaths were performed correctly only with a median of 6.7 and 0.0%, respectively.…”
Section: Discussioncontrasting
confidence: 80%
“…It is remarkable that the participants were able to reach almost perfect compression depth during chest compressions and rescue breaths directly after the training and in the follow-up examination. These results are better than results of other studies ( 38 , 39 ). As a limitation, it must be mentioned that pre-training compression depth and rescue breaths were performed correctly only with a median of 6.7 and 0.0%, respectively.…”
Section: Discussioncontrasting
confidence: 80%
“…New education methods might not necessarily replace existing methods, but they may be ideal options for CPR instructors to implement in circumstances such as the COVID-19 pandemic or where close-contact restrictions apply. Previous studies have reported that the average retention length of CPR knowledge and skill was 3 months after an education intervention [20][21][22][23][24][25][26]. Due to a spike of COVID-19 cases in Taiwan, the present study could only observe the length of retention till 1 month after the intervention.…”
Section: Plos Onementioning
confidence: 74%
“…Studies have indicated that hybrid CPR education approaches effectively improve participant knowledge, attitude, skill, and intention to CPR [13,18]. The retention length of CPR knowledge and skill after CPR education courses has also been considered a measurement of CPR education effectiveness, with previous studies having reported an average retention length of CPR knowledge and skill of 3 months after an education intervention [20][21][22][23][24][25][26]. However, there is lack of evidence measuring the results of attitude, and intention to do CPR, and then combining it with length of retention after CPR education.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos evidenciam que a simulação aumenta a percepção do clima de segurança do paciente na terapia do AVE agudo e reduz diretamente o tempo médio de atendimento em 12 minutos, assim como aumenta o número de pacientes que são trombolizados em menos de 30 minutos (TAHTALI et al, 2017;JANG et al, 2020), tornando claro o impacto positivo dessas atividades durante o processo de formação dos alunos. O AVE é uma das emergências mais frequentes nos prontos-socorros, e, para condução do atendimento a esta doença na fase aguda, são exigidos conhecimentos, habilidades, equipe multiprofissional e ações em uma curta janela de tempo (TAHTALI et al, 2017).…”
Section: Discussionunclassified